Financial Management of Muhammadiyah Senior Secondary School: Manajemen Keuangan Pendidikan SMA Muhammadiyah - Sahlan , Muhammad Muad; Hidayatulloh, Hidayatulloh (Indonesian Journal of Education Methods Development, 2020)
This research was conducted on the basis of the importance of school financial management in carrying out the wheels of education which can have an impact on improving the quality of the school itself. Therefore, the research was conducted to identify and provide analysis of the implementation of education financial management, which includes planning, organizing, implementing, controlling and accountability at SMA Muhammadiyah 1 Taman and the factors that influence its implementation. The research method used is qualitative by using a descriptive approach to describe the phenomena that occur in this institution. SMA Muhammadiyah 1 Taman is the object of research because it has implemented financial management well, marked by the rapid fulfillment of learning facilities and the dynamics of ongoing school activities. From the research results it is known that: 1) management of education financial management, SMA Muhammadiyah 1 Taman has utilized information technology, utilizes bank service products, and financial management software. the implementation of financial management is in accordance with the stages, starting from: a) planning to compile activities, planning budgets, and determining sources of financial revenue; b) the organization includes the principal, treasurer, staff treasurer of revenue, staff of expenditure treasurers, treasurer of BOS, treasurer of BPOPP, wakasek as executor of activities; c) the implementation of activities has been carried out in accordance with the planned activity program, while the realization of the budget for budget planning is less than 100% due to the arrears of tuition fees and student activity funds that have not been paid 100% by the parents of students; d) financial management control is carried out by i) the principal of the school treasurer and budget users, ii) the government to the principal regarding the use of BOS and BPOPP funds, iii) the Muhammadiyah organization to the school principal in relation to the supervision and guidance of financial management sourced from parents students, and; e) accountability for the use of the budget is carried out by i) the treasurer and executor of activities to the principal, ii) the principal to the government regarding the use of BOS and BPOPP funds, and the principal to the Muhammadiyah organization related to funds sourced from the parents of students.